Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Manifeste des femmes québécoises - Un groupe de femmes québécoises. (L'étincelle, 1971)
En décembre 1971, les éditions L'Étincelle ont publié en effet le Manifeste des femmes québécoises, opuscule de 58 pages, imprimé sur papier brouillon. «Ce manifeste circule à Montréal depuis quelques mois, sous forme polycopiée à faible tirage. Nous croyons qu'il mérite une plus grande diffusion», explique l'éditeur. L'ouvrage et la préface sont signés «Un groupe de femmes de Montréal».
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Un groupe de femmes de Montréal - Un groupe de femmes québécoises. (Manifeste des femmes québécoises, 1971)
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; histoire et politique; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques